High-temperature structural disorders stabilize hydrous aluminosilicates in the mantle transition zone - Baoyun Wang; Jin Liu; Yanyao Zhang; Baisheng Nie; Wei Yang; Jialong Hao; Xing Ding; Yongjun Tian (Nature Communications)
Abstract Hydrous aluminosilicates are important deep water-carriers in sediments subducting into the deep mantle. To date, it remains enigmatic how hydrous aluminosilicates withstand extremely high temperatures in the mantle transition zone. Here we systematically investigate the crystal structures and chemical compositions of typical hydrous aluminosilicates using single-crystal X-ray diffraction, electron probe microanalyzer, and nanoscale secondary ion mass spectrometry. These single crystals are synthesized at 15.5–22.0 GPa and 1400–1700 °C, featuring pervasive structural disorders. In particular, Al and Si atoms extensively occupy new tetrahedral and octahedral sites that are nominally vacant in their ordered counterparts. High temperature activates disorders leading to variable local crystal structures and more hydrogen incorporation into the crystal structure. This result suggests that the order-to-disorder transition holds the key to the high thermal stability of hydrous aluminosilicates, significantly affecting the water cycle in the deep mantle.